Static inflation and deflation pressure–volume curves from excised lungs of marine mammals - Fahlman, Andreas; Loring, Stephen H.; Ferrigno, Massimo; Moore, Colby D.; Early, Greg A.; Niemeyer, Misty E.; Lentell, Betty J.; Wenzel, Frederick W.; Joy, Ruth; Moore, Michael J. (Journal of Experimental Biology, 2011)
Author Posting. © The Author(s), 2011. This is the author's version of the work. It is posted here by permission of The Company of Biologists for personal use, not for redistribution. The definitive version was published in Journal of Experimental Biology 214 (2011): 3822-3828, doi:10.1242/jeb.056366. Excised lungs from 8 marine mammal species (harp [Pagophilus groenlandicus], harbor [Phoca vitulina], and gray seal [Halichoerus grypus], Atlantic white-sided [Lagenorhynchus acutus], common [Delphinus delphis] and Risso's dolphin [Grampus griseus], long finned pilot whale [Globicephala melas], and harbor porpoise [Phocoena phocoena]) were used to determine minimum air volume of the relaxed lung (MAV, n = 15) and the elastic properties (pressure-volume curves, n = 24) of the respiratory system, and total lung capacity (TLC). Our data indicate that mass-specific TLC (sTLC, l • kg-1) does not differ between species or groups (odontocete vs. phocid) and agree with that estimated (TLCest) from body mass (Mb) by: TLCest = 0.135 • Mb 0.92. Measured MAV was on average 7% of TLC, with a range from 0% to 16%. The pressure-volume curves were similar among species on inflation but diverged during deflation in phocids as compared with odontocetes. These differences provide a structural basis for observed species differences in depth at which lungs collapse and gas exchange ceases. This project was supported by a grant from the Office of Naval Research (ONR award number N00014-10-1-0059; Dr. Loring was supported by HL 52586 from the National Institutes of Health. 2012-11-15